Acceleration and speed profiles by playing position in elite women`s handball: Insights from the EHF EURO 2024 - Ramírez, A. G.; Lozano, D.; Cartón-Llorente, A.; Manchado, C. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Recent rule changes in team handball have increased the relevance of sprinting and acceleration for performance outcomes. This study aimed to evaluate the acceleration-velocity profiles of elite female players during the Final Weekend of the Women`s EURO 2024.